Stability of Li- and Mn-Rich Layered-Oxide Cathodes within the First-Charge Voltage Plateau. Issue 8 (21st June 2016) - Iddir, Hakim; Bareño, Javier; Benedek, Roy
Abstract : Li and Mn rich layered oxides x Li2 MnO3 (1- x )Li M O2 enable high capacity and energy density Li-ion batteries, but undergo structural transformations during the first charge that degrade their performance, and result in Voltage Fade upon cycling. First-principles density-functional-theory simulations reveal atomic transformations that occur in the bulk during the first charge. The simulations and experiment (particularly XRD) show that the O and Mn sublattices remain intact during the early part of the voltage plateau, and significant transformations occur only well into the voltage plateau, with perhaps close to half of the Li in the Li2 MnO3 domains removed. That Voltage Fade is actually observed experimentally for a first charge with only minimal activation (extending only slightly beyond the onset of the voltage plateau) may be a consequence of surface and interface instabilities. Implications for the achievement of high energy-density, low-fade battery operation are discussed.